2021
DOI: 10.1001/jamanetworkopen.2021.33406
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Factors Associated With Older Adults’ Cancer Screening Decision-making

Abstract: IMPORTANCE Decisions for older adults (aged Ն65 years) and their clinicians about whether to continue to screen for cancer are not easy. Many older adults who are frail or have limited life expectancy or comorbidities continue to be screened for cancer despite guidelines suggesting they should not; furthermore, many older adults have limited knowledge of the potential harms of continuing to be screened. OBJECTIVETo summarize the patient-reported factors associated with older adults' decisions regarding screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“… 28 , 30 , 41 , 42 , 43 , 44 Literature also supports that lay people generally overestimate the benefits of participation. 23 , 26 , 27 , 45 A Danish study examined responses to mammography screening and revealed that it provided feelings of reassurance for those participating, compared with women not invited to screening. 30 Another Danish interview study also found that women with false‐positive results did not blame medical technology or lose confidence in screening but continued to desire participation despite their negative experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 , 30 , 41 , 42 , 43 , 44 Literature also supports that lay people generally overestimate the benefits of participation. 23 , 26 , 27 , 45 A Danish study examined responses to mammography screening and revealed that it provided feelings of reassurance for those participating, compared with women not invited to screening. 30 Another Danish interview study also found that women with false‐positive results did not blame medical technology or lose confidence in screening but continued to desire participation despite their negative experiences.…”
Section: Discussionmentioning
confidence: 99%
“…An American study shows that 74.1% of American women older than 74 years undergo breast cancer screening despite the US Preventive Task Force recommendation not to. 25 Previous work addressing the communication of discontinuing mammography screening supported that women feel devalued when discontinued from screening, 23 , 51 , 52 and perceived inviting older women to screen as a symbol that society still cares about them. 31 The participants in our study intuitively assumed that age‐related discontinuation from screening was a case of ageism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this investigation, we employed a modified definition of BCAM that does not include older age as a non-modifiable factor, which consequently led to more challenging questions and decreased levels of awareness. This decision was made based on the observation that peak breast cancer incidence in Chinese women occurs around menopause, rather than increasing with age (7). Gaining knowledge of non-modifiable risk factors not only enables women to assess their own risk but also encourages adherence to routine screening and timely diagnosis (8).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Yet, many people do not receive cancer screening due to lack of awareness, lack of access to health care, and cost. 18,19 In order to fill the knowledge gaps in behavioral risk factors among agricultural producers, the Nebraska Cancer Prevention Survey was explicitly designed to study a wide range of cancer risk and preventive behaviors including cancer screening (cervical, breast, skin, colorectal, and prostate cancers), fruit and vegetable intake, physical activity, tan-…”
Section: Introductionmentioning
confidence: 99%